Long-term echocardiographic assessment of descendants of gestational breast cancer patients exposed to anthracycline-based chemotherapy. (25th November 2020) - Oneto Fernandez, M; Gonzalez-Manzanares, R; Garcia-Duran, C; Mesa Rubio, D; Ruiz Ortiz, M; Delgado Ortega, M; Rodriguez Almodovar, A.M; Romo Penas, E; De La Haba, J; Castillo Dominguez, J.C
Abstract: Background: Breast cancer is the most common cancer in women and the leading cause of cancer death in women. Although gestational breast cancer (GBC) accounts only for a small amount of diagnosis, the incidence is increasing due to delayed childbearing. Treating GBC is a significant challenge, having to maintain a balance between effective treatment for the patient and safety for the descendants. Anthracycline-based chemotherapy (AC) remains to be the systemic treatment of choice in many GBC patients. Although AC in GBC appears to be safe for the descendants, data on the long-term cardiotoxic effects of AC are scarce. Purpose: To evaluate long-term cardiotoxicity on descendants of GBC patients exposed to AC during pregnancy or breastfeeding. Methods: We retrospectively recruited descendants of GBC patients and classified them according to AC exposure (case group and non-exposed control group). We performed a thorough echocardiographic assessment. Results: We identified 7 GBC patients that received AC during pregnancy (n=6) or breastfeeding (n=1). All of them were diagnosed during the second or third trimester. Median cumulative anthracycline dose was 508mg/m 2 . A total of 8 cases and 5 controls were recruited. Median age at echocardiographic assessment was 10 years in cases and 8 years in controls. None of them had known prior cardiac disease. Echocardiographic parameters were within normal values in both groups (Table 1). Conclusion: A long-term echocardiographic assessment showed no abnormalities in a series of descendants of GBC exposed to AC during pregnancy or breastfeeding. This study may contribute to a better understanding of the safety for the descendants of AC during pregnancy or breastfeeding. Funding Acknowledgement: Type of funding source: None